2014
DOI: 10.5604/15093492.1128840
|View full text |Cite
|
Sign up to set email alerts
|

Back Pain in Mothers of Cerebral Palsied Children

Abstract: 1. Long-term daily care of children with cerebral palsy promotes the development of back pain in their mothers. 2. The incidence and intensity of pain depends primarily on the child's functional status and independence level, body weight, age, the need for repeatedly lifting the disabled child throughout the day and the number of additional tasks performed by the mother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Long-term responsibility for a disabled child, combined with a necessity to face adversities and challenges associated with handling the child, frequently leads to negative emotions, such as anxiety, sadness, anger, hopelessness and distress, experienced by the person, and adversely affecting the functioning of the parents and the entire family [13,14,15]. The most common effects of long-lasting caregiver burden include depressive and anxiety disorders of varied intensity [1,6,16,17,18,19,20,21,22,23,24,25,26]. However, intensity of anxiety and depressive symptoms in the parents is not related exclusively to predictors associated with the child’s disability, but is also linked to personal, social and economic variables resulting from the parents’ needs and health status as well as factors occurring in the family; this fact reflects the multidimensional effects of these determinants in health-related quality of life (HRQOL) in individuals taking care of children with CP [27].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term responsibility for a disabled child, combined with a necessity to face adversities and challenges associated with handling the child, frequently leads to negative emotions, such as anxiety, sadness, anger, hopelessness and distress, experienced by the person, and adversely affecting the functioning of the parents and the entire family [13,14,15]. The most common effects of long-lasting caregiver burden include depressive and anxiety disorders of varied intensity [1,6,16,17,18,19,20,21,22,23,24,25,26]. However, intensity of anxiety and depressive symptoms in the parents is not related exclusively to predictors associated with the child’s disability, but is also linked to personal, social and economic variables resulting from the parents’ needs and health status as well as factors occurring in the family; this fact reflects the multidimensional effects of these determinants in health-related quality of life (HRQOL) in individuals taking care of children with CP [27].…”
Section: Introductionmentioning
confidence: 99%
“…Posluszny et al (2015) reported that parents of children with disabilities are more exposed to cervical spine pain, which can be explained by the static and dynamic overload, common in the caregiver's activity postures (Knibbe & Knibbe, 2012; Nelson & Baptiste, 2006). Long‐term daily care of children with disabilities seems to favour their mothers' low back pain, and the intensity of this pain is associated with the child's level of functionality and independence, body weight, age and the number of additional tasks performed by mothers (Czupryna et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As falas indicam a indispensabilidade de um maior apoio psicológico e social para essas famílias, incluindo visitas domiciliares da equipe multidisciplinar. Por se tratar de uma condição crônica, as crianças necessitam de altos níveis de apoio parental, social e educacional, enfatizando que continuarão a exigir indefinidamente altos níveis de cuidados básicos pessoais aos cuidadores, no caso, os pais e familiares envolvidos; isso pode gerar prejuízos na saúde e qualidade vida dos pais, incluindo sintomas de depressão, ansiedade e dores musculares (17,29) . A insegurança foi relatada pelos participantes no que concerne ao conhecimento com profundidade pela equipe de saúde sobre a "nova" microcefalia pelo mosquito, conforme relatos dos familiares, por ser uma doença de causas e consequências diferentes das "outras microcefalias": Não se pode esquecer que, por ser uma condição da atualidade emergencial e relativamente nova, as informações sobre o ZIKV e seus efeitos em mulheres grávidas, fetos, recém-nascidos, lactentes e crianças, incluindo outras complicações neurológicas e comorbidades associadas, são gradualmente conhecidas e disponibilizadas para a sociedade, à medida que as pesquisas avançam, o que causa bastante desconforto na sociedade, principalmente nas equipes de saúde e famílias envolvidas.…”
Section: Microcefalia Por Vírus Zika E As Mudanças No Contexto Familiarunclassified